Effectiveness of Early Warning Score (EWS) in Pre, Intra, and Post Dialysis: A Systematic Review - Evi Kartika Maharani; Ika Yuni Widyawati; Ika Nur Pratiwi (Indonesian Journal of Global Health Research, 2025)
The Early Warning Score (EWS) is a crucial tool for detecting early signs of clinical deterioration in hemodialysis (HD) patients. However, previous research has primarily focused on the intra-dialysis phase, necessitating a systematic review to explore the effectiveness of EWS across all phases (pre, intra, and post-dialysis). Objective: This study aims to assess the effectiveness of EWS in detecting complications in hemodialysis patients across these three phases and to evaluate its impact on morbidity, mortality, length of hospital stays, and readmission rates. Methods: This systematic review was conducted following PRISMA guidelines. Literature searches were performed in databases such as PubMed, Scopus, ScienceDirect, ProQuest, and Google Scholar. The keywords used in the search were “Early Warning Score” OR “EWS” AND “Hemodialysis” OR “Renal Dialysis” OR “Dialysis” AND “Pre-dialysis” OR “Intradialysis” OR “Post-dialysis” and can utilize Boolean logic (AND, OR, or NOT) to maximize search results. The screening of articles with respect to limitations including year 2016 - 2024. Results: Out of 1,246 identified articles, 15 studies met the inclusion criteria. The findings indicate that EWS is effective in detecting complications across all hemodialysis phases, with significant improvements in clinical management and reductions in morbidity and mortality rates. Conclusion: The comprehensive application of EWS in the pre, intra, and post-dialysis phases can enhance the safety of hemodialysis patients.